(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the history of the formation and development of joint stock business in the Republic of Uzbekistan in 1989-1996. The complexity of the stages of formation of a joint-stock business, their reasons, as well as the further deepening of reforms that led to the formation of market relations and the development of joint-stock business in the republic are shown.